Ucieczka od zacofania? Polska transformacja jako projekt modernizacyjny - Tymiński, Maciej; Koryś, Piotr (Roczniki Dziejów Społecznych i Gospodarczych, 2015)
An escape from backwardness? The Polish transformation as a modernization project (Summary) The authors discuss the late professor Jacek Kochanowicz’s views on Poland’s backwardness and its modernization in the period of the country’s transformation after 1989. The main purpose of the article is to reconstruct Kochanowicz’s interpretation of the process of the systemic transformation, understood as a modernization project. In the paper the authors begin by presenting Kochanowicz’s opinions on the causes of Poland’s backwardness, especially those originating in Polish history. The discussion of the way Kochanowicz saw the causes of Poland’s backwardness is followed by the exposition of the way in which he interpreted the process of Poland’s transformation. In conclusion, the authors attempt to outline Kochanowicz’s view of Poland’s development in the following decades, stressing his skepticism as to the country’s chances of a rapid and successful modernization.